Two-dimensional ultrasound and two-dimensional shear wave elastography on femoral and saphenous neuropathy in patients with type 2 diabetes mellitus - Song, Yang; Zhang, Ying; Zhang, Yuhong; Hu, Bin (Frontiers in Neurology, 2022)
Objective: This study aims to observe the value of two-dimensional (2D) ultrasound and two-dimensional shear wave elastography (2D-SWE) in evaluating femoral nerve (FN) and saphenous nerve (SN) neuropathy in patients with type 2 diabetes mellitus (T2DM). Materials and methods: According to the diabetic peripheral neuropathy (DPN) diagnostic criteria, 60 T2DM patients were enrolled and divided into 35 T2DM patients without DPN (non-DPN group) and 25 T2DM patients with DPN (DPN group). The control group consisted of another 15 healthy volunteers. The width, thickness, cross-sectional area (CSA), and perimeter of FN and SN were measured with 2D ultrasound. The average shear wave velocity (SWV) of FN and SN was measured by 2D-SWE. Parameters of the left and right lower extremities were compared in each group, and the above parameters were compared among groups. The correlations between ultrasonographic and laboratory parameters were evaluated, and the independent influencing factors of SWV of FN and SN were analyzed. Results: The width, thickness, CSA, perimeter and SWV of FN and SN in the DPN group were greater than those in the non-DPN groups and control group (P<0.05). The width, thickness, CSA, perimeter and SWV of FN and SN in the non-DPN group were greater than those in the control group (P<0.05). The CSA of FN was positively correlated with FPG, HbA1c and TG (r=0.34–0.69, P<0.01). The perimeter of FN was positively correlated with FPG, HbA1c and TG (r=0.37–0.68, P<0.01). The perimeter of FN were negatively correlated with IgF-1(r=-0.31, P<0.05). The CSA of SN was positively correlated with FPG and TG (r=0.26–0.42, P<0.05). The perimeter of SN was positively correlated with FPG, TG (r=0.37-0.39, P<0.01). The SWV of FN and SN were positively correlated with FPG and TG (r=0.35–0.57, P<0.01; r=0.43–0.49, P<0.01). FPG and TG were independent influencing factors of the SWV of FN and SN (P<0.05). Conclusion: 2D ultrasound and 2D-SWE could be used to non-invasively, objectively, and accurately evaluate the abnormal changes of the FN and SN in patients with T2DM.